“The Dictionary of the Terminology of Theology” at a Glance - Hoorieh Shojaee (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Each science has its own terminology and technical language, which is a tool for understanding the texts of that science. Dictionaries are an application tool for researchers. The dictionaries help the correct and quick understanding of these terms in order to co-ordinate with the scientific community and also help them in their further search. The subject of this article is the critique of the book of “the dictionary of the Terminology of Theology, the Islamic Theology, the New Theology, the Religions” by Moslem Mohammadi, a graduate of the majoring in theology and philosophy. So, while introducing the book in general, it refers to some of the structural and content characteristics as well as its positive and negative aspects. In a critical review, the book's articles were checked for the authenticity of the text, the accuracy of the documentation, and the amount of utilization of valid sources. We conclude that the book has some drawbacks in terms of its form, content, and the observance of the principles of the research method. So this book has not fulfilled its mission in explaining and describing some of the terminology of theology. Therefore, its totality cannot be a reliable source for the selection of scholars. In the end, suggestions are made to overcome the shortcomings and enhance the work.